Antitumor effectiveness and mechanism of action of Ru(II)/amino acid/diphosphine complexes in the peritoneal carcinomatosis progression. Issue 10 (October 2017) - Mello-Andrade, Francyelli; da Costa, Wanderson Lucas; Pires, Wanessa Carvalho; Pereira, Flávia de Castro; Cardoso, Clever Gomes; Lino-Junior, Ruy de Souza; Irusta, Vicente Raul Chavarria; Carneiro, Cristiene Costa; de Melo-Reis, Paulo Roberto; Castro, Carlos Henrique; Almeida, Marcio Aurélio Pinheiro; Batista, Alzir Azevedo; et al.
Peritoneal carcinomatosis is considered as a potentially lethal clinical condition, and the therapeutic options are limited. The antitumor effectiveness of the [Ru(l -Met)(bipy)(dppb)]PF6 (1) and the [Ru(l -Trp)(bipy)(dppb)]PF6 (2) complexes were evaluated in the peritoneal carcinomatosis model, Ehrlich ascites carcinoma–bearing Swiss mice. This is the first study that evaluated the effect of Ru(II)/amino acid complexes for antitumor activity in vivo. Complexes1 and2 (2 and 6 mg kg −1 ) showed tumor growth inhibition ranging from moderate to high. The mean survival time of animal groups treated with complexes1 and2 was higher than in the negative and vehicle control groups. The induction of Ehrlich ascites carcinoma in mice led to alterations in hematological and biochemical parameters, and not the treatment with complexes1 and2 . The treatment of Ehrlich ascites carcinoma–bearing mice with complexes1 and2 increased the number of Annexin V positive cells and cleaved caspase-3 levels and induced changes in the cell morphology and in the cell cycle phases by induction of sub-G1 and G0/G1 cell cycle arrest. In addition, these complexes reduce angiogenesis induced by Ehrlich ascites carcinoma cells in chick embryo chorioallantoic membrane model. The treatment with the LAT1 inhibitor decreased the sensitivity of the Ehrlich ascites carcinoma cells to complexes1 and2 in vitro—which suggests that the LAT1 could be related to the mechanism of action of amino acid/ruthenium(II) complexes, consequently decreasing the glucose uptake. Therefore, these complexes could be used to reduce tumor growth and increase mean survival time with less toxicity than cisplatin. Besides, these complexes induce apoptosis by combination of different mechanism of action.